FIB Secondary Etching Method for Fabrication of Fine CNT Forest Metamaterials - Pander, Adam; Hatta, Akimitsu; Furuta, Hiroshi (Nano-Micro Letters, 2017)
Anisotropic materials, like carbon nanotubes (CNTs), are the perfect substitutes to overcome the limitations of conventional metamaterials; however, the successful fabrication of CNT forest metamaterial structures is still very challenging. In this study, a new method utilizing a focused ion beam (FIB) with additional secondary etching is presented, which can obtain uniform and fine patterning of CNT forest nanostructures for metamaterials and ranging in sizes from hundreds of nanometers to several micrometers. The influence of the FIB processing parameters on the morphology of the catalyst surface and the growth of the CNT forest was investigated, including the removal of redeposited material, decreasing the average surface roughness (from 0.45 to 0.15 nm), and a decrease in the thickness of the Fe catalyst. The results showed that the combination of FIB patterning and secondary etching enabled the growth of highly aligned, high-density CNT forest metamaterials. The improvement in the quality of single-walled CNTs (SWNTs), defined by the very high G/D peak ratio intensity of 10.47, demonstrated successful fine patterning of CNT forest for the first time. With a FIB patterning depth of 10 nm and a secondary etching of 0.5 nm, a minimum size of 150 nm of CNT forest metamaterials was achieved. The development of the FIB secondary etching method enabled for the first time, the fabrication of SWNT forest metamaterials for the optical and infrared regime, for future applications, e.g., in superlenses, antennas, or thermal metamaterials.